Ketamine and Pulmonary Oedema-Report of Two Cases - S Parthasarathy; M Ravishankar; S Selvarajan; T Anbalagan (Indian Journal of Anaesthesia, 2009)
Perioperative pulmonary oedema is one of the most challenging complications faced by anaesthesiologists. In most of the instances, coronary artery disease, valvular heart diseases, hypertension may precipitate pulmonary oedema due to increased hydrostatic pressure while acid aspiration, airway obstruction may cause it due to increased vascular permeability. In a few instances, acute pulmonary oedema can present in an otherwise healthy patient to cause diagnostic difficulties. We report two such cases of intra operative pulmonary oedema with the use of ketamine which were identified and managed successfully. The most probable cause is also described.